2021
DOI: 10.3390/jcm10225456
|View full text |Cite
|
Sign up to set email alerts
|

Low Brachial Artery Flow-Mediated Dilation Predicts Worse Prognosis in Hospitalized Patients with COVID-19

Abstract: Background: Endothelial injury can be induced by coronavirus disease 2019 (COVID-19) and seems to exert a crucial pathogenic role in its most severe clinical manifestations. We aimed to investigate the association between brachial artery flow-mediated dilation (bFMD), a potential clinical and non-invasive measure of endothelial function, and in-hospital prognosis of COVID-19 patients. Methods: Brachial artery flow-mediated dilation was assessed in hospitalized COVID-19 patients within 48 h of hospital admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 43 publications
1
26
1
Order By: Relevance
“…Indirectly, measurement of parameters such as blood viscosity and vWF have been used to understand whether there is an impact on hemodynamics [24] , [78] , [79] . It has also been shown that low brachial artery flow-mediated dilation, a marker of endothelial dysfunction, predicts an unfavorable in-hospital prognosis in COVID-19 patients [80] , [81] .…”
Section: Overview Of the Pathophysiology Of Thrombosismentioning
confidence: 99%
“…Indirectly, measurement of parameters such as blood viscosity and vWF have been used to understand whether there is an impact on hemodynamics [24] , [78] , [79] . It has also been shown that low brachial artery flow-mediated dilation, a marker of endothelial dysfunction, predicts an unfavorable in-hospital prognosis in COVID-19 patients [80] , [81] .…”
Section: Overview Of the Pathophysiology Of Thrombosismentioning
confidence: 99%
“…Similarly, it was reported that lower FMD values were found in patients who had radiographic signs of pneumonia compared with those who did not. [ 14 ] This is another important finding showing that there is a relationship between the severity of the Covid-19 and low FMD values.…”
Section: Discussionmentioning
confidence: 89%
“…It is also the first study in which patients were objectively grouped according to lung parenchyma involvement and compared in terms of FMD%. Indeed, in some recent studies in which FMD was evaluated in patients with recent or ongoing Covid-19, [ 14 , 15 ] however, the correlation between FMD% and biochemical parameters of the patients such as d-dimer, troponin, ferritin, LDH, and WBC has not been directly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Third, since liver dysfunction may be a clinical feature of severe COVID-19, lower TC and LDL-C levels have been hypothesized to result from reduced lipoprotein synthesis by dysfunctional hepatocytes in the most severe clinical forms of COVID-19 [ 29 ]. Fourth, as microcirculation is damaged and vascular permeability increases with increasing COVID-19 severity [ 36 ], it has been suggested that an abnormal distribution of lipoproteins from the intravascular to the extravascular space may contribute to reduce circulating TC and LDL-C in severe COVID-19 [ 19 , 29 ]. Of note, all these mechanisms are intriguing and biologically well-founded.…”
Section: Discussionmentioning
confidence: 99%